2015
DOI: 10.1007/s00180-015-0612-8
|View full text |Cite|
|
Sign up to set email alerts
|

Smoothing combined generalized estimating equations in quantile partially linear additive models with longitudinal data

Abstract: This paper develops a robust and efficient estimation procedure for quantile partially linear additive models with longitudinal data, where the nonparametric components are approximated by B spline basis functions. The proposed approach can incorporate the correlation structure between repeated measures to improve estimation efficiency. Moreover, the new method is empirically shown to be much more efficient and robust than the popular generalized estimating equations method for non-normal correlated random err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…with C 1 defined in (18), and c = c 0 𝜅 * f l . Proposition S3 shows that the event  rsc (a, b, c) holds with probability at least 1 − (2p…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…with C 1 defined in (18), and c = c 0 𝜅 * f l . Proposition S3 shows that the event  rsc (a, b, c) holds with probability at least 1 − (2p…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Fu and Wang, 15 Tang and Leng, 16 and Leng and Zhang 17 all indicated that the efficiency of the parameter estimation will be lost when a strong correlation exists. To capture the correlation and enhance the estimation efficiency, Lv et al 18 used the smooth‐threshold efficient QR‐based generalized estimating equations to select the covariates and estimate the parameters in the quantile partially linear additive model with longitudinal data; Wang and Sun 19 explored this kind of method for the quantile partial linear varying coefficient model with longitudinal data.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the centered spline basis function approximation, we propose two new imputed estimating equation methods to estimate the component functions using the smooth-threshold estimating equation proposed in Ueki [9]. The variable selection method based on the smooth-threshold estimating equation can avoid the convex optimization of the penalized variable selection procedure, and has been extended to some models, such as Li et al [10], Zhao and Li [11], Lv et al [12] and Geronimia and Saportab [13]. In the present paper, based on the marginal imputed estimating equation and the maximum correlation imputed estimating equation, we define two smooth-threshold estimating equations to study model (1) with missing response at random.…”
Section: Introductionmentioning
confidence: 99%